Kearifan Lokal Masyarakat Penambang Minyak Tradisional dalam Bahasa dan Budaya Jawa di Desa Wonocolo Kabupaten Bojonegoro - Sartika, Anjar Dwi; Fateah, Nur (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
This study aims to identify and describe the cognition system (cognition system) and local wisdom (local wisdom) in oil mining which is traditionally managed by the people of Wonocolo Village, Bojonegoro Regency. This study used a descriptive qualitative which is studied ethnolinguistically with ethnoscience model. The data in this study were oral data obtained when the researcher observed the participants by using interview and filled note techniques in order to obtain the data classified from predrilling process and drilling process to find out cognition system and local wisdom of it. Key Wordsi: Traditional Oil Mining, Local Wisdom, Ethnolinguistics